Cautiousness, stereotypy, and variability in older and younger adults. - Lopatto, David E.; Ogier, Stacy; Wickelgren, Emily A. (Psychological Record)
Older adults and college students were tested with two procedures that measure stereotypy and response variability. In Experiment 1 subjects guided a marker through a 6 by 6 matrix by pressing two computer keys. Points were awarded on either a continuous or variable ratio 3 schedule of reinforcement. Points were exchanged for money. Continuous reinforcement produced significantly higher stereotypy than intermittent reinforcement did in both age groups. A difference was found in stereotypy between age groups during the variable ratio schedule. This difference may have been caused by the greater task anxiety of the older adults. In Experiment 2 subjects were tested using the matrix procedure with the consequence that response variability was differentially reinforced. Four levels of variability were tested in the two age groups. Both older and younger subjects learned to vary response patterns to obtain points. The results are discussed in the context of cautiousness as an age-related explanation for behavior. Reprinted by permission of the publisher.